2023
DOI: 10.3390/horticulturae9030368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan and Micro-Carbon-Based Phosphorus Fertilizer on Strawberry Growth and Productivity

Abstract: High fertilization rates and pesticides are required for the intensive production of strawberries, which offer several therapeutic health benefits. Recently, chitosan (CHI), and phosphorus fertilizer based on Micro Carbon TechnologyTM (MCT-P) were applied to encourage strawberry sustainable production and enhance phosphorus-use efficiency. Field trials were conducted throughout 2020/2021 and 2021/2022, to evaluate the effectiveness of MCT–P and CHI in improving strawberry cv. Fortuna growth and yield as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Failure to harvest in a timely manner will lead to excessive maturity of strawberries, decreased overall quality, and easy decay [4]. Strawberry growers need to frequently observe the growth of strawberries in farmland to plan harvesting decisions [5]. Therefore, it is necessary to study a method to quickly obtain the overall growth information of strawberry fields during the harvesting stage, provide growth status information, assist in planning the harvesting plan, ensure that strawberries are harvested in a timely manner at the appropriate stage during the peak harvest period, and improve product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to harvest in a timely manner will lead to excessive maturity of strawberries, decreased overall quality, and easy decay [4]. Strawberry growers need to frequently observe the growth of strawberries in farmland to plan harvesting decisions [5]. Therefore, it is necessary to study a method to quickly obtain the overall growth information of strawberry fields during the harvesting stage, provide growth status information, assist in planning the harvesting plan, ensure that strawberries are harvested in a timely manner at the appropriate stage during the peak harvest period, and improve product quality.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, exogenous green ecological preparations have frequently been applied in facility production to alleviate the adverse damage caused by negative conditions through the regulation of plant growth, the increase in disease resistance and immunity, and finally, the enhancement of quality and growth in yield [6][7][8]. This approach is regarded as a primary technical solution to the aforementioned production challenges with relatively minimal investment and rapid outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that oligosaccharides, as plant growth regulators, can regulate physiological and biochemical reactions in plant cells when exposed to biotic or abiotic stresses [9][10][11]. Recently, chitosan, a type of polysaccharide, has been widely used on facility crops due to its antibacterial, non-toxic, and environmentally friendly characteristics [6,7,12]. Chitosan is a polymer composed of several thousand glucosamine units, extracted from chitin (a N-acetylglucosamine polymer) in shrimp and crab shells following deacetylation under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan can be used as antitranspirant and stimulate the physiological responses to mitigate the adverse effects of abiotic stresses through enhancement of antioxidant enzymes, photosynthetic rate and stomatal closure (O'Herlihy et al, 2003;El-Mougy et al, 2006;Hidangmayum et al, 2019). In addition, chitosan stimulates the production of osmotic adjustment compounds such as organic acids, sugars and amino acids (Hidangmayum et al, 2019) leading to improve plant health and yields (Metwaly et al, 2023). Since chitosan can inhibit the growth of different pathogens (Vasyukova et al, 2001), it can be used as alternative to chemical fungicides (O'Herlihy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%